The effect of silver diamine fluoride on the remineralization of early enamel carious lesions under pH-cycling conditionsWhy Is This Important? - Parand Sorkhdini, DVM, PhD; Yasmi O. Crystal, DMD, MSc, FAAPD; Qing Tang, MS; Frank Lippert, PhD (JADA Foundational Science)
Background: This study explored the in vitro anticaries efficacy of silver diamine fluoride (SDF) in remineralizing early enamel carious lesions. Methods: Lesions were created in human enamel specimens, which were divided into 5 groups (n = 36): SDF (38%), SDF and potassium iodide (SDF and KI), potassium fluoride (KF), silver nitrate (AgNO3), and deionized water (DIW). Treatments were applied once. Groups were divided into 2 subgroups (n = 18), pH cycled for 5 days with twice-daily treatments with either fluoride or DIW. Vickers hardness number measurements were conducted at each stage. Data were analyzed using a 2-way analysis of variance. Results: The 2-way analysis of variance for ΔVickers hardness number was significant (P < .0001). In both pH-cycling models (with or without fluoride), SDF, SDF and KI, and KF promoted more remineralization than AgNO3 and DIW (P < .0001). In the presence of twice-daily fluoride treatments, there was no difference between SDF, SDF and KI, and KF (P = .4577). However, in the absence of fluoride treatments, SDF promoted more remineralization than SDF and KI and KF (P < .0001). There were no differences between SDF and KI and KF (P = .4577 and P = .2156; pH-cycling models with and without fluoride, respectively) and AgNO3 vs DIW (P = .6553 and P = .1194). Conclusion: With the copresence of fluoride, SDF and SDF and KI equally promote remineralization of enamel lesions. KI impairs SDF-related remineralization in the absence of fluoride treatments.